2016
DOI: 10.15698/mic2016.11.537
|View full text |Cite
|
Sign up to set email alerts
|

How do yeast sense mitochondrial dysfunction?

Abstract: Apart from energy transformation, mitochondria play important signaling roles. In yeast, mitochondrial signaling relies on several molecular cascades. However, it is not clear how a cell detects a particular mitochondrial malfunction. The problem is that there are many possible manifestations of mitochondrial dysfunction. For example, exposure to the specific antibiotics can either decrease (inhibitors of respiratory chain) or increase (inhibitors of ATP-synthase) mitochondrial transmembrane potential. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 91 publications
0
31
0
Order By: Relevance
“…Generation and accumulation of intracellular ROS was prominent in C. albicans 10231 cells treated with [C 16 MIM][Cl] (Figure 7). In yeasts, ROS are majorly produced in the mitochondria (Knorre et al, 2016). High ROS levels are detrimental as they cause oxidative damage to intracellular molecules and cell membrane lipids .…”
Section: Mechanism Of Action Of Antifungal Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generation and accumulation of intracellular ROS was prominent in C. albicans 10231 cells treated with [C 16 MIM][Cl] (Figure 7). In yeasts, ROS are majorly produced in the mitochondria (Knorre et al, 2016). High ROS levels are detrimental as they cause oxidative damage to intracellular molecules and cell membrane lipids .…”
Section: Mechanism Of Action Of Antifungal Ionic Liquidsmentioning
confidence: 99%
“…High ROS levels are detrimental as they cause oxidative damage to intracellular molecules and cell membrane lipids . Interestingly, ROS production is one of the mechanisms by which yeast cells senses mitochondrial dysfunction (Knorre et al, 2016). The mitochondrial dysfunction in C. albicans 10231 cells was assessed by ψ m and dehydrogenases activity.…”
Section: Mechanism Of Action Of Antifungal Ionic Liquidsmentioning
confidence: 99%
“…Consequently, a Cys–SOH chaperone, Ybp1, brings together Orp1 and Yap1 into a ternary complex that selectively activates condensation of the Orp1 to provide specificity in the transfer of oxidising equivalents by a reactive sulphenic acid species [ 105 ]. In yeast, respiratory complex III deficiencies could then be compensated by a ROS modulation of the Yap1 signalling process [ 106 ].…”
Section: Mitochondrial Deficiencies and Their Impact Through Ros Signmentioning
confidence: 99%
“…The maximum ATP content of yeast in the hyperosmotic medium with 4 g L −1 KCl addition occurred at metaphase, with 168.45% of control, while with 10% (v v −1 ) ethanol present, 10 g L −1 KCl addition led to the maximum ATP content, with 201.64% of control. The result indicated that KCl supplementation could promote ATP synthesis and then improve functionality of mitochondrial, which could enable the cells to resist stress from hyperosmotic or ethanol stress (Knorre et al , ). It also should be noted that 4 or 10 g L −1 KCl, rather than a higher concentration, exhibited the best promotion activity, which probably because that KCl could not absorb into cells completely (Casey et al , ).…”
Section: Resultsmentioning
confidence: 99%